L’écriture de soi, et ses modalités de constitution en archives - Anouk Cohen (Ateliers d'Anthropologie)
The Equality and Reconciliation Commission (IER: Instance Equité et Réconciliation), created in Morocco in 2006, aims to “establish the truth about several historical facts” (from the date of Moroccan independence, 1956, to the end of the reign of Hassan II, 1999). Faced with a lack of official archives, the IER proceeded to archive prison books recently published in Morocco. This raises a number of questions: how did prison stories shift from the status of literary compositions to that of archives? How is the link between the notions of “testimony”, “stories” and “archives” conceived and manipulated by the actors who use them (IER, authors, publishers, readers), and why attribute this terminology to them? These questions lie at the heart of this study, which focuses on the processes underlying this transformation of prison books into archives.